Counseling Methods for Handling Sexual Harassment Cases: Analysis Of Steps In Supporting Victims At DPPPA Palembang - Hurriyati, Dwi; Rachmadi, Muhammad Nazrey; Diana, Diana (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The purpose of this study is to analyze the factors analyzing the effectiveness of procedures for handling sexual harassment cases, evaluating the supporting and inhibiting factors in the process of handling sexual harassment cases because the victim feels embarrassed and afraid to be shunned because of the sexual harassment that befalls the victim, then afraid of the opposite sex because the victim feels traumatized by what he has experienced, feels afraid to speak because the victim has been threatened by the perpetrator who committed the harassment. Method: The method used is counseling, which is the process of providing assistance carried out by an expert to individuals experiencing a problem with three stages, namely building confidence, providing assistance that leads to solving the problems faced by clients. action stage. Practical Applications: The outcomes of this community service benefit victims of sexual violence and communities with similar experiences. By improving counseling skills, this activity (community service) contributes to community development efforts especially for victims of sexual abuse. Conclusion: This study underscores the importance of appropriate counseling interventions in helping victims like RNA overcome trauma and restore their psychological health, paving the way for further research in this area.